Holocene environmental change inferred from multiple proxies in the mouth of Gomso Bay on the west coast of South Korea. Issue 2 (26th July 2017) - Song, Bing; Yi, Sangheon; Chang, Tae-Soo; Kim, Jin-Cheul; Mao, Limi; Nahm, Wook-Hyun; Jia, Hongjuan
Abstract: A sediment core (14DH-C01) obtained from the mouth of Gomso Bay, on the west coast of South Korea, was used to obtain high-resolution palynomorph, grain-size, and 14 C age data to investigate the Holocene sedimentary environment. The results indicated a transgressive depositional process with four stages controlled by sea-level change, as follows: river-dominated fluvial deposition from the early Holocene to 8.48 cal ka BP; tide-dominated tidal channel fill transgression from 8.48 to 8.08 cal ka BP; tide- to wave-dominated tidal channel fill transgression from 8.08 to 6.98 cal ka BP; and wave-dominated marine transgression from 6.98 cal ka BP to the present. Tidal channel filling was the primary mid-Holocene depositional process, accounting for the high sedimentation rate observed. The different hydrodynamics of the river-dominated, tide-dominated, tide- to wave-dominated, and wave-dominated processes following the changes in sea level may have controlled the transgressive depositional process. This transgressive sedimentary model differs from those of other large river mouth areas (e.g., the Changjiang River) since the mid-Holocene, perhaps resulting from the limited sediment supply in the study area.